Vera Zasulich's Critique of Neo-Populism: Party Organisation and Individual Terrorism in the Russian Revolutionary Movement (1878-1902) - Gaido, Daniel Fernando (2015)
Vera Zasulich’s shooting of Trepov, a governor of St Petersburg who had ordered the flogging of a political prisoner, in January 1878, catapulted her to international fame as a revolutionary heroine, a reputation that she put to good use by becoming one of the five ‘founding parents’ of Russian Marxism that created the ‘Group for the Emancipation of Labour’ in 1883. But her act of self-sacrifice also triggered, to her dismay, the institutionalisation of individual terrorist tactics in the Russian Populist movement with the creation of the ‘People’s Will’ (Narodnaya Volya) Party in 1879. The organisation went into decline after the killing of Tsar Alexander II in 1881, and Populism itself was increasingly superseded by Marxism as the hegemonic force on the left with the rise of the Russian Social Democratic Labour Party (RSDLP). But individualterrorist tactics reappeared with the creation of the Socialist Revolutionary Party in 1902, prompting Zasulich to write an article for Die neue Zeit, the theoretical organ of German Social Democracy, in which she both condemned the Neo-Populist tendency as deleterious to the rising labour movement and supported the organisational plans for the RSDLP sponsored by the Iskra group, developed at length by Lenin in his book What Is to Be Done?, published in March 1902. This article provides the background to Vera Zasulich’s article ‘The Terrorist Tendency in Russia’ (December 1902), setting it against the history of the Russian revolutionary movement from 1878 to 1902.